Answer:
D. -8x-54
Step-by-step explanation:
Apply the distributive property.
6-4(3(2x)+3*5-4x)
Multiply 2 by 3
6-4(6x+15-4x)
Multiply 3 by 5
6-4(6x+15-4x)
Subtract 4x from 6x
6-4(2x+15)
Apply the distributive property.
6-4(2x)-4*15
Multiply 2 by -4
6-8x-4*15
Mutliply -4 by 15 6-8x-60
Subtract 60 from 6
Answer:
x= 1/2
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
1x+3=x+10x−2
x+3=x+10x+−2
x+3=(x+10x)+(−2)(Combine Like Terms)
x+3=11x+−2
x+3=11x−2
Step 2: Subtract 11x from both sides.
x+3−11x=11x−2−11x
−10x+3=−2
Step 3: Subtract 3 from both sides.
−10x+3−3=−2−3
−10x=−5
Step 4: Divide both sides by -10.
−10x/−10=−5/−10x=1/2
Answer:
Answer:.1.77
Step-by-step explanation:
e^x = 5.9
Take the natural logarithm of both sides
x = ln (59/10)
x = 1.77
(found this)
I believe it would be (-2,-2) i may be wrong though i dont have my graphing papers